Antioxidant, anti-inflammatory and antidiabetic activities of the combination of Curcuma longa (Zingiberaceae), Aframomum melegueta (Zingiberaceae) and Piper guineensis (Piperaceae) compared to plants alone - Mayele, Blanchard M.; Mbadiko, Clément M.; Mubwele, Armandine; Nyamangombe, Gustave I.; Kabamba, Nadège N.; Ngbolua, Koto-Te-Nyiwa; Mbemba, Théophile F. (Orapuh Journal, 2025)
Introduction Diabetes mellitus is a group of diseases characterized by chronic hyperglycemia resulting from a disturbance in insulin secretion, function, or both. It is currently one of the major public health problems.PurposeThe aim of this study was to quantify secondary metabolites, evaluate the biological activities of individual plants, and assess the combination's antioxidant, anti-inflammatory, and antidiabetic activities compared to the plants used individually.Methods To conduct this study, we examined the qualitative and quantitative composition of some metabolites using conventional methods. We assessed the antioxidant activities in vitro using DPPH• and ABTS• radicals. The antidiabetic activity was evaluated using the glucose oxidase method, while the anti-inflammatory activity was determined in vitro using the protein denaturation method (albumin).Results Our findings revealed that the CAP combination contained all the investigated metabolites, and the concentrations of polyphenols, flavonoids, and tannins were higher than those of the individual plants. The anti-inflammatory and antidiabetic activities of CAP were superior for both extracts, although the antioxidant activity of CAP was lower compared to C. longa and A. melegueta for organic extracts on the ABTS• radical.Conclusion The combination of these plants could be a prudent choice as part of a strategy to combat diabetes, particularly through herbal medicine.